Inhibition of Autophagy by Estradiol Promotes Locomotor Recovery after Spinal Cord Injury in Rats - Lin, Chao-Wei (Neurosci Bull, 2016)
17β-estradiol (E2) has been shown to have neuroprotective effects in different central nervous system diseases. The mechanisms underlying estrogen neuroprotection in spinal cord injury (SCI) remain unclear. Previous studies have shown that autophagy plays a crucial role in the course of nerve injury. In this study, we showed that E2 treatment improved the restoration of locomotor function and decreased the loss of motor neurons in SCI rats. Real-time PCR and western blot analysis revealed that the protective function of E2 was related to the suppression of LC3II and beclin-1 expression. Immunohistochemical study further confirmed that the immunoreactivity of LC3 in the motor neurons was down-regulated when treated with E2. In vitro studies demonstrated similar results that E2 pretreatment decreased the autophagic activity induced by rapamycin (autophagy sensitizer) and increased viability in a PC12 cell model. These results indicated that the neuroprotective effects of E2 in SCI are partly related to the suppression of excessive autophagy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12264-016-0017-x) contains supplementary material, which is available to authorized users.